Vitiligo, From Physiopathology to Emerging Treatments: A Review - Migayron, Laure (Dermatol Ther (Heidelb), 2020)
Vitiligo is a chronic inflammatory skin disease leading to the loss of epidermal melanocytes. To date, treatment options for vitiligo patients are limited, lack sustained efficacy, and are mainly based on off-label use of immunosuppressive agents, such as systemic or topical steroids or topical calcineurin inhibitors, in association with the use of ultraviolet light. However, recent insights into the understanding of the immune pathogenesis of the disease have led to the identification of several therapeutic targets and the development of targeted therapies that are now being tested in clinical trials. In this review, based on the physiopathology of the disease, we summarize emerging targets that could be developed for the treatment of vitiligo and discuss recent and ongoing developments of drugs for the management of the disease.